2019
DOI: 10.1177/8755122519859976
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antifungal Guidelines in Malignant Hematology Patients: A Review of the Literature

Abstract: Objective: To review the published literature assessing adherence rates to antifungal guidelines and reasons for nonadherence in the adult malignant hematology inpatient setting. Data sources: The databases Embase, MEDLINE, and PubMed (from data inception to May 2019) were searched using the terms hematology, oncology, antifungal, guidelines, adherence, and stewardship with the search limited to adult human subjects and published in English. This yielded 123 articles. From this list, studies that were publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, there may be circumstances that warrant a deviation from treatment guidelines; a simple assessment of guideline adherence is an imperfect measure of appropriateness, particularly within the context of an immunocompromised haematology population. 75 Expert consensus has supported the use of many of the National Antimicrobial Prescribing Survey (NAPS) programme's appropriateness metrics to assess antifungal prescribing quality. 39 In the NAPS programme, appropriateness is evaluated relative to an institution's compliance with national and/or local guidelines in terms of indication, choice of agent, dose selection and duration, as well as whether appropriate streamlining has occurred (e.g.…”
Section: Antifungal Prescribing Quality Metricsmentioning
confidence: 99%
“…However, there may be circumstances that warrant a deviation from treatment guidelines; a simple assessment of guideline adherence is an imperfect measure of appropriateness, particularly within the context of an immunocompromised haematology population. 75 Expert consensus has supported the use of many of the National Antimicrobial Prescribing Survey (NAPS) programme's appropriateness metrics to assess antifungal prescribing quality. 39 In the NAPS programme, appropriateness is evaluated relative to an institution's compliance with national and/or local guidelines in terms of indication, choice of agent, dose selection and duration, as well as whether appropriate streamlining has occurred (e.g.…”
Section: Antifungal Prescribing Quality Metricsmentioning
confidence: 99%
“…However, studies have shown that antifungal prescribing guidelines are not consistently adhered to, and inappropriate antifungal prescribing remains a clinical concern, especially in inpatient settings. 10 , 21 , 22 …”
Section: Discussionmentioning
confidence: 99%